PROBLEMATIKA KONTRAK BAKU DALAM AKAD MUDHARABAH DI LEMBAGA PERBANKAN SYARIAH (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
The development of  financing in Islamic banks illustrates that this productenjoyed by many people. Financing is one option the community to cooperatewith the banks, with a profit-sharing system. This paper aims to examine theproblematic raw deal in mudharabah in Islamic banking. These problems willhave an impact on the lives of  customers, where customers will feel aggrievedover contract made unilaterally. At first these customers want to get capital fortheir business because of  the content of  the burdensome contracts, selection of customers simply leave or not so do the financing by banks. If  the customeraccepts the contract of  cooperation, we can be sure the customer is running witha full big responsibility. In addition, the ratio of  part of  the customer will beless commensurate with the contribution of  cooperation that customers provide.